2011
DOI: 10.1080/09670262.2011.590902
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, fine structure, life cycle and phylogenetic analysis ofPhyllosiphon arisari, a siphonous parasitic green alga

Abstract: Phyllosiphon arisari Ku¨hn (Phyllosiphonaceae, Chlorophyta) commonly occurs in Arisarum leaves in coastal Mediterranean areas of the Iberian Peninsula and Balearic islands. The genus Phyllosiphon was first considered to be a member of the Xanthophyceae but was later transferred to the chlorophytes. However, there are few data about its morphology, ultrastructure, ecology or phylogenetic affinities. In this paper we describe the morphology of Phyllosiphon, as studied in field material and in culture; the fine s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 29 publications
0
26
0
Order By: Relevance
“…K. bambusicola was isolated from a tropical ecosystem and K. apyrenoidosa was found in a part of the Mediterranean with a humid subtropical climate, according to the Köppen-Geiger climate classification system (Peel et al, 2007). In addition, the phylogenetically closely related genera Heveochlorella and Phyllosiphon were also found in various subtropical or tropical subaerial localities (Zhang et al, 2008;Aboal & Werner, 2011). Therefore, we expect that additional taxa of the Heterochlorella lineage might be discovered in the little-known phototrophic microbial biofilms of these habitats.…”
Section: Discussionmentioning
confidence: 99%
“…K. bambusicola was isolated from a tropical ecosystem and K. apyrenoidosa was found in a part of the Mediterranean with a humid subtropical climate, according to the Köppen-Geiger climate classification system (Peel et al, 2007). In addition, the phylogenetically closely related genera Heveochlorella and Phyllosiphon were also found in various subtropical or tropical subaerial localities (Zhang et al, 2008;Aboal & Werner, 2011). Therefore, we expect that additional taxa of the Heterochlorella lineage might be discovered in the little-known phototrophic microbial biofilms of these habitats.…”
Section: Discussionmentioning
confidence: 99%
“…Kalinella apyrenoidosa, one of the two species of the genus Kalinella, was recently described from a sub-Mediterranean corticolous sample (Neustupa et al, 2013a). The life cycle of a peculiar and little-known genus Phyllosiphon, another member of the Watanabea clade, probably includes chlorelloid subaerial individuals, as well as siphonaceous parasitic populations thriving in the leaves of the subtropical vascular plant genus Arisarum (Aboal & Werner, 2011;Hallmann et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Our analyses, expanded by newly acquired 18S rDNA and rbcL gene sequences from parasitic populations of the Phyllosiphon from infected leaves of Arisarum vulgare in Sardinia and Croatia, show that these microalgae represent a single homogenous lineage that was previously identified as P. arisari (Aboal & Werner 2011, Procházková et al 2015a. However, phylogenetic investigation of parasitic specimens isolated from infected leaves of Arum italicum showed that these parasitic microalgae formed a lineage separated from P. arisari.…”
Section: Discussionmentioning
confidence: 58%
“…The only known DNA sequences of the parasitic members of the Phyllosiphon were acquired from infected leaves of subtropical Arisarum vulgare (Aboal & Werner 2011, Procházková et al 2015a). Interestingly, several recent studies demonstrated that populations closely related to those obtained from parasitic populations thriving within the leaves of A. vulgare also occur in various subaerial microhabitats throughout Europe as free-living microalgae (Cutler et al 2013, Hallmann et al 2013, Procházková et al 2015a.…”
Section: Introductionmentioning
confidence: 99%